Psikoanalisis Agama Sigmund Freud: Analisis Kritis Dalam Perspektif Hindu - Ni Made Devi Pebriani (Widya Katambung, 2026)
This study is motivated by the strong influence of Sigmund Freud’s thought, which views religion as an infantile illusion and a form of universal neurosis, while simultaneously giving rise to the problem of reductionism by simplifying religion merely as a product of individual psychological conflict. In many religious traditions, including Hinduism, however, religion encompasses ontological, spiritual, and transcendental dimensions that cannot be reduced solely to psychological explanations. This study aims to analyze Freud’s psychoanalytic concept of religion, including religion as an expression of the Oedipus Complex in Totem and Taboo, religion as a childhood illusion, and religion as a neurotic disorder, while critically examining these concepts from the perspective of Hindu teachings as reflected in the Bhagavadgītā. This research employs a qualitative method with a library research approach through hermeneutic and comparative analyses of Freud’s works and Hindu literature. The findings indicate that Freud’s perspective tends to be reductionistic and demonstrates limitations in explaining the transpersonal dimensions of spirituality within Hinduism. From the Hindu perspective, particularly in the teachings of the Bhagavadgītā, religion is neither an illusion nor a neurosis, but rather a path of self-realization that integrates the psychological, ethical, and metaphysical dimensions of human existence toward moksha. Therefore, this study underscores the importance of a cross-perspective approach in understanding religion in a more holistic and comprehensive manner.